Pedagogical and Psychological Training During the Use of Foreign Experiences in the Application of Innovative Educational Technologies - Rashidova Nodira Abdullo qizi (European Science Publishing, 2023)
The article analyses special features of using innovative technologies in teaching process. At present, advanced innovative technologies are one of the main essential components of the educational activity of any educational institution. Innovation is a new one, designed to ensure gradual development, improvement of the system, its transition to a qualitatively new level of development. At present, it is usual to divide innovative technologies into technological and methodological parts this classification is based on the specificity and place of application of innovations. Technological innovations in the field of education (training) are the use of modern information environment, software and computer technologies that affect the learning process, allowing you to build new schemes of interactive modes and individual approaches in the "teacherstudent" relationship. Methodological innovations are innovations in the field of methods of training and education, teaching and learning, and the organization of the educational process. In modern times, this is the most common type of innovation, covering almost the entire education system.
Keywords: Innovative technologies, learning process, type of innovation, interactive methods, approach, and teacher-student.